Математическое моделирование гидрогазодинамических процессов в вихревой трубке - Крамской, А.В.; Кудрявцев, И.Н.; Самохвал, И.А. (Проблемы машиностроения, 2011)
Для описания гидрогазодинамических процессов в вихревой трубке Ранке–Хилша предложена математическая модель, учитывающая основные особенности ламинарных и вихревых течений вязкой жидкости или газа. Математическая модель может быть использована для компьютерного моделирования методом конечных объёмов основных термодинамических и гидрогазодинамических параметров вихревой трубки Ранке–Хилша. Для опису гідрогазодинамічних процесів у вихровій трубці Ранке–Хілша запропоновано математичну модель, що враховує основні особливості ламінарних і вихрових течій в’язкої рідини чи газу. Математична модель може бути використана для комп’ютерного моделювання методом скінченних об’ємів основних термодинамічних та гідрогазодинамічних параметрів вихрової трубки Ранке–Хілша. The mathematical model which uses Reynolds-averaged Navier–Stokes equations has been pro-posed in present paper for description of the hydro & gas dynamic processes in the Ranque-Hilsch vortex tube. These equations describe both laminar and turbulent flows of a viscous liquid or gas in different directions. The k– turbulence model in the formulation of Menter is used. The mathematical model proposed takes into account the main features of the laminar and tur-bulent flows of a viscous liquid or gas and can be used for computer simulation by finite volume analysis of the main thermodynamic and hydro & gas dynamic parameters of the Ranque–Hilsch vortex tube.